Lineyte-samarnon folk songs as representations of the ethno-linguistic identity of the culture of Leyte and Samar. - Lagarde, Stephen Q. (Danyag :the UPV journal of humanities and social sciences, 2004)
This paper argues that folk songs may, indeed, serve as vehicles through which the inherent character and worldview of a given culture may be analyzed and investigated. It adheres to the notion that "folk songs serve as an index to our identity as a people" (Banas, 1969). In order to demonstrate this, it takes as an example the cultural prejudice that the Warays of Leyte and Samar have, through the years, endured. It takes their folk songs as pieces of evidence that may point out that the Waray-speaking people of Leyte and Samar have a shared historical and cultural experience with the rest of the Christianized Filipinos. They are as Pinoy as all other ethno-linguistic groups in the Philippines.